PENGARUH PERMAINAN CODING UNPLUGGED TERHADAP KEMAMPUAN BERPIKIR LOGIS ANAK USIA 5-6 TAHUN DI TK PERTIWI II TELANAIPURA - Hotmauli Damanik, Meirani; Hasni, Uswatul; Indriani Harianja, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted due to the limited application of learning activities aimed at developing logical thinking skills in early childhood at TK Pertiwi II Telanaipura. Observations indicated that the logical thinking abilities of children aged 5–6 years had not developed optimally, as shown by difficulties in recognizing patterns, sequencing, classifying objects, distinguishing sizes, and demonstrating constructive thinking. This study aimed to examine the effect of unplugged coding games on the logical thinking abilities of children aged 5–6 years.The research used a quantitative approach with a pre-experimental one-group pretest–posttest design. The sample consisted of 12 children. Data were collected through observation using a validated instrument and analyzed using hypothesis testing. The results showed a significant improvement in logical thinking abilities, with a t-value of 24.163 exceeding the t-table value of 2.201 at α = 0.05. The mean score increased from 21.5 to 42.5, and the effect size analysis (Cohen’s d = 5.24) indicated a strong effect. These findings conclude that unplugged coding games significantly improve children’s logical thinking abilities.